Effects of Nutritional Education On Knowledge And Snack Foods Election of Junior High School Students - Husnah Husnah; Sakdiah Sakdiah; Siti Hajar; Siti Zubaidah (Proceedings of AICS - Social Sciences, 2021)
Snack is a type of food that is widely consumed in everyday life, especially by school-age students. The selection of snacks by students generally does not pay attention to the nutritional value, safety and cleanliness. Unhealthy snacks have an unfavorable impact on health, this can occur due to lack of knowledge. Nutritional education is a media for delivering information about problems and nutritional content. The purpose of this study was to determine the effect of nutritional education on knowledge and the selection of snacks for students. This research was conducted from 7 to 15 February 2020 with the research sample in the form of all VII and VIII grade students in one of the public junior high school in Banda Aceh and the type of this research is analytical experimental method with one group pretest and posttest design. Sampling is taken by probability sampling with a simple random sampling technique that taken based on the students attendance number which is interspersed with one number and so on. Pretest and posttest data about the knowledge of 85 students were tested statistically with the Wilcoxon test and showed that 91.8% of students had good knowledge but after nutritional education there was an increase to 95.3%, meanwhile 35.3% of students who had good behavior in choosing types of snacks after receiving nutritional education increased to 54.1 %. It can be concluded that nutritional education has an effect on increasing knowledge and behavior in choosing types of snacks (p = 0.001 and Z = -3.78) in students at one of the public junior high school in Banda Aceh.Keywords: Nutritional education, snacks, knowledge, the selection of snacks.